Inovasi Produk Anyaman Pandan dengan Menerapkan Strategi Desain dalam Produk Modern - Kendall Malik; Ferry Fernando; Yandri; Saftrian Mukhlizul Fuad; Nofrial; Ramadhani Kurniawan; Hanafi Malik (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study aims to analyze local pandan woven products in West Sumatra, especially Sijunjung Regency, into a more modern product innovation form through strategic design. Pandanus weaving has a long history and strong cultural value but faces challenges such as declining demand due to shifting market preferences and competition from manufactured goods. Using a qualitative and explorative approach through the